Correlations and repeatability between Babesia spp. infection levels using two dairy cattle breeding systems - Giglioti, Rodrigo; de Oliveira, Henrique Nunes [UNESP]; Gutmanis, Gunta; Luciani, Guilherme Favero; Azevedo, Bianca Tainá; de Carvalho Fiorin, Cristiane Fernandes; de Andrade, Mariana Fogale; Silva, Marco Antônio Faria; Vercesi Filho, Anibal Eugênio; Katiki, Luciana Morita; Okino, Cintia Hiromi; de Sena Oliveira, Márcia Cristina; et al. (Springer Nature, 2020)
Babesia bovis and Babesia bigemina are tick-transmitted piroplasms that cause severe damage to the livestock industry in tropical regions of the world. Recent studies demonstrated differences in infection levels of these haemoparasites among bovine breeds and variation between individual cows regarding resistance to these diseases. This study aimed to estimate the repeatability and correlations between B. bovis and B. bigemina using two cattle breeding systems, an individual system (IS) and a collective paddock system (CPS). All animals were Holstein breed, and the levels of B. bovis and B. bigemina in blood samples were estimated by quantitative polymerase chain reaction (qPCR). The estimated correlations for the B. bigemina and B. bovis DNA copy number for IS and CPS were moderate and high, respectively, whereas repeatability estimates for both systems and both Babesia species were moderate. Although we cannot infer that the type of rearing system directly influenced the correlation and repeatability coefficients, it appears that the bovine parasitemia burden may be dependent on (or determine) the parasitemia burden on ticks because the bovines remained in the same place for a longer time in both systems. Thus, the babesiosis infection levels of the ticks may have been uniform, a phenomenon that also ensures greater uniformity in cattle infection. This factor may have favored the occurrence of infected ticks leading to higher repeatability estimates and correlations. Our study confirms high variability in resistance/susceptibility between breeds, and the high correlations found may be linked to this characteristic and the most intensive breeding type of dairy cattle. Besides, under the present study conditions, the estimated correlations suggest that measuring an infection level of one Babesia species can predict the level of infection of the other.
Keywords: Bovine babesiosis; Breeding system; Correlation; Infection; Repeatability